Mechanical properties of ceramic-polymer nanocomposites (eXPRESS Polymer Letters)
Nano crystalline powders of Barium Sodium Niobate (BNN) with the composition Ba3–2x Na4+x R Nb10 O30 with (R stands for rare earth = 0, x = 0) have been prepared by conventional ceramic technique. Barium Sodium Niobate can form a wide range of solid solutions, incorporating rare earth and alkali, alkaline earth elements with different compositions. The powder belonged to tungsten bronze type structure with tetragonal symmetry and lattice constants a = b = 1.2421 nm and c = 0.3903 nm. XRD (X-ray Diffraction) SEM (Scanning Electron Microscope) and AFM (Atomic Force Microscope) studies revealed that the particle size is in the nanometer range. Composites are prepared by mixing powders of BNN with polystyrene at different volume fractions of the BNN. Melt mixing technique is carried out in a Brabender Plasticoder at a rotor speed of 60 rpm (rotations per minute) for composite preparation. Mechanical properties such as stress-strain behavior, Young’s modulus, tensile strength, strain at break etc. are evaluated. Addition of filler enhances the mechanical properties of the polymer such as Young’s modulus and tensile strength. The composites showed the trend of perfect adhesion between the filler and the polymer. The filler particles are distributed relatively uniform fashion in all composites and the particles are almost spherical in shape with irregular boundaries. To explore more carefully the degree of interfacial adhesion between the two phases, the results are analyzed by using models featuring adhesion parameter. The experimental results are compared with theoretical predictions.